The role of creative accounting practices in developing methods of fraud and tax evasion - Samah, Bahoura; Meriem, Chanbi (The International tax journal, 2025)
This study aims to shed light on creative accounting practices because of the role they play in developing methods of fraud and tax evasion from the point of view of tax investigators, by clarifying the aspects of creative accounting and its practices, studying the motives and methods of institutions to adopt these practices and the nature of creative accounting, as well as identifying the following: The concept of fraud and tax evasion and its relationship to creative accounting, and finding ways to combat or reduce their severity in light of accounting and tax reforms by referring to what is stated in jurisprudence and international references through international accounting standards and legal texts related to the Algerian financial accounting system and tax legislation using the descriptive and analytical approach.